2012
DOI: 10.1177/0974930612449534
|View full text |Cite
|
Sign up to set email alerts
|

Rural Housing and Risks for Children’s and Women’s Health: Estimates for Rajasthan State, India

Abstract: This article is concerned with the prevalence of unhealthy housing (UH) in the rural areas of the state of Rajasthan, India. UH is defined to be the houses that are made with non-permanent materials and those that lack a supply of clean water and proper sanitation. Habitation in such houses poses a health risk, particularly for children and women. The Indian government has initiated various programmes to increase the provision of healthy housing for low-income rural families. However, the progress of these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These houses are usually built by community members using traditional methods and short-lived natural materials found in the areas near the village (such as soil, mud, wood, straw, and leaves) using architecture and building technologies closely related to ancestral traditions. 22,23 Several studies have shown the relationship of vector-borne diseases such as malaria, dengue, and Chagas disease with traditional architectural practices and features of rural housing, including mud walls, thatched roofs, open eaves, and unscreened windows. [24][25][26][27][28] In the case of leishmaniasis, information available about house-related risk factors is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…These houses are usually built by community members using traditional methods and short-lived natural materials found in the areas near the village (such as soil, mud, wood, straw, and leaves) using architecture and building technologies closely related to ancestral traditions. 22,23 Several studies have shown the relationship of vector-borne diseases such as malaria, dengue, and Chagas disease with traditional architectural practices and features of rural housing, including mud walls, thatched roofs, open eaves, and unscreened windows. [24][25][26][27][28] In the case of leishmaniasis, information available about house-related risk factors is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Baru et al (2010) analysed inequities in access to health services. Katrak (2012) pointed to inequities in household sanitation as between the rural and urban areas. Sampat (2007) reports that even within the rural areas there are significant inequities between households.…”
Section: Introductionmentioning
confidence: 99%